2023
DOI: 10.3389/fnbeh.2023.1162009
|View full text |Cite
|
Sign up to set email alerts
|

Icariin reduces cognitive dysfunction induced by surgical trauma in aged rats by inhibiting hippocampal neuroinflammation

Abstract: Postoperative cognitive dysfunction (POCD) is a common postsurgical complication in elderly individuals, significantly impacting the quality of life of patients; however, there is currently no effective clinical treatment for POCD. Recent studies have shown that Icariin (ICA) has antiaging effects and improves cognitive function, but its effect in POCD has not been studied. In this study, we investigated the influence of ICA on cognitive function and the TLR4/NF-κB signaling pathway in a POCD rat model. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Numerous clinical and preclinical studies have confirmed a strong correlation between neuroinflammation and cognitive disorders, including Alzheimer’s disease and stress-related cognitive impairment [ 35 , 36 ]. Therapies targeting neuroinflammation have also shown promising results in alleviating cognitive dysfunctions [ 37 , 38 ]. Microglia are emerging as critical key regulators of the inflammatory response process in the central nervous system; overactivation of these cells might impair cognition through the excessive release of inflammatory cytokines [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical and preclinical studies have confirmed a strong correlation between neuroinflammation and cognitive disorders, including Alzheimer’s disease and stress-related cognitive impairment [ 35 , 36 ]. Therapies targeting neuroinflammation have also shown promising results in alleviating cognitive dysfunctions [ 37 , 38 ]. Microglia are emerging as critical key regulators of the inflammatory response process in the central nervous system; overactivation of these cells might impair cognition through the excessive release of inflammatory cytokines [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a later study established a causal relationship between HMGB1 and PND by reporting that inhibition of HMGB1 via its neutralizing antibody effectively mitigated PND in aged rats undergoing partial hepatolobectomy (Terrando et al, 2016). Several drugs exert their pharmacological effects through the inhibition of various molecules within the HMGB1/TLR4/NF-κB pathway, resulting in reduced hippocampal inflammatory responses, suppressed microglial activation, mitigated neuronal injury and attenuated surgery-induced memory impairment (Wang et al, 2022(Wang et al, , 2023Yao et al, 2023). As for the glymphatic system, there are limited studies associated with this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical trauma induces the release of pro‐inflammatory cytokines and chemokines at the site of tissue injury, initiating a local inflammatory response. These inflammatory mediators can activate peripheral immune cells, such as macrophages and monocytes, which then infiltrate the CNS and further contribute to the neuroinflammatory cascade 10,11 . In the hippocampus, microglia, the resident immune cells of the brain, play a key role in sensing and responding to these inflammatory signals 12 .…”
Section: Introductionmentioning
confidence: 99%
“…These inflammatory mediators can activate peripheral immune cells, such as macrophages and monocytes, which then infiltrate the CNS and further contribute to the neuroinflammatory cascade. 10 , 11 In the hippocampus, microglia, the resident immune cells of the brain, play a key role in sensing and responding to these inflammatory signals. 12 Microglia activation is a complex process involving the transformation of microglia into an activated phenotype, characterized by morphological changes and the release of pro‐inflammatory cytokines, such as tumour necrosis factor α (TNF‐α) and interleukin‐1β (IL‐1β).…”
Section: Introductionmentioning
confidence: 99%